Peran Literasi Keuangan dan Penggunaan Produk Perbankan terhadap Perencanaan Keuangan Rumah Tangga di Provinsi Bali - I Gusti Ayu Made Agung Mas Pratiwi Andriani (Ikatan Da'i Indonesia, 2025)
Households represent a core economic unit that plays a strategic role in maintaining macroeconomic stability through consumption, saving, and investment activities. Financial planning quality determines household resilience to economic uncertainty and its contribution to aggregate demand. Changes in income patterns and the expansion of the informal sector in Indonesia increase the complexity of household financial management. Inflationary pressure and rising living costs further highlight the importance of systematic financial planning, particularly in Bali Province where the economy is strongly influenced by tourism dynamics. Financial literacy serves as a foundation for households to allocate resources rationally and adopt a long-term financial perspective. Banking products function as operational tools that support efficient and measurable financial planning. This study aims to analyze the contribution of financial literacy and the utilization of banking products to household financial planning in Bali Province. The research method applies a literature review by examining academic publications, official institutional reports, and relevant references. Research findings indicate that improved financial literacy enhances budgeting capability, saving discipline, debt management, and financial risk control. Utilization of banking products such as savings accounts, credit services, and digital banking strengthens financial planning effectiveness when supported by adequate understanding. Integration of financial literacy and banking access creates a more adaptive and sustainable household financial system. Research recommendations emphasize strengthening community-based financial education, developing simple and inclusive banking products, and promoting regional policy support oriented toward improving household welfare in Bali Province.